Everywhere/nowhere : gender mainstreaming in development agencies - Tiessen, Rebecca. 1970- (Bloomfield, CT : Kumarian, 2007)
"Gender mainstreaming emerged in early gender and development work and gained strength following the 1975 Conference on Women in Mexico City. After three decades of gender and development approaches, and a more recent emphasis on gender mainstreaming, Everywhere/Nowhere presents a timely reflection on the challenges and opportunities development agencies have faced as they attempt to translate gender mainstreaming policies into practice."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Sex discrimination against women; Non-governmental organizations